In Planta Glycan Engineering and Functional Activities of IgE Antibodies - Montero-Morales, Laura; Maresch, Daniel; Crescioli, Silvia; Castilho, Alexandra; Ilieva, Kristina M.; Mele, Silvia; Karagiannis, Sophia N.; Altmann, Friedrich; Steinkellner, Herta (Frontiers in Bioengineering and Biotechnology, 2019)
Human immunoglobulin E (IgE) is the most extensively glycosylated antibody isotype so glycans attached to the seven N-glycosites (NGS) in its Fab and Fc domains may modulate its functions. However, targeted modification of glycans in multiply glycosylated proteins remains a challenge. Here, we applied an in vivo approach that allows the manipulation of IgE N-glycans, using a trastuzumab equivalent IgE (HER2-IgE) as a model. Taking advantage of plant inherent features, i.e. synthesis of largely homogeneous complex N-glycans and susceptibility to glycan engineering, we generated targeted glycoforms of HER2-IgE largely resembling those found in serum IgE. Plant-derived HER2-IgE exhibited N-glycans terminating with GlcNAc, galactose or sialic acid, lacking or carrying core fucose and xylose. We were able to not only modulate the five NGSs naturally decorated with complex N-glycans, but to also induce targeted glycosylation at the usually unoccupied NGS6, thus increasing the overall glycosylation content of HER2-IgE. Recombinant human cell-derived HER2-IgE exhibited large N-glycan heterogeneity. All HER2-IgE variants demonstrated glycosylation-independent binding to the target antigen and the high affinity receptor FcεRI, and subsequent similar capacity to trigger mast cell degranulation. In contrast, binding to the low affinity receptor CD23 (FcεRII) was modulated by the glycan profile, with increased binding to IgE variants with glycans terminating with GlcNAc residues. Here we offer an efficient in planta approach to generate defined glycoforms on multiply glycosylated IgE, allowing the precise exploration of glycosylation-dependent activities.